2014
DOI: 10.1111/sji.12165
|View full text |Cite
|
Sign up to set email alerts
|

High‐Mobility Group Box 1 Inhibition Alleviates Lupus‐Like Disease in BXSB Mice

Abstract: High-mobility group box 1 protein (HMGB1), a ubiquitous nuclear DNAbinding protein, functions as a potent proinflammatory factor. In this study, we evaluated the effects of HMGB1 inhibition on murine lupus using the lupusprone model. We treated male BXSB mice with neutralizing anti-HMGB1 monoclonal antibody (HMGB1 mAb) from age 16 weeks to 26 weeks. The control group received the same amount of control IgG. Lupus-prone male BXSB mice treated with HMGB1mAb showed attenuated proteinuria, glomerulonephritis, circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 26 publications
0
24
1
Order By: Relevance
“…The results presented here appear to contradict a recent study by Zhang et al (36) showing that treatment with anti-HMGB1 antibodies reduced lupus-like disease, including proteinuria and glomerulonephritis, in lupus-prone BXSB mice (36). Lupus in BXSB mice is characterized by lymph node and spleen enlargement, hypergammaglobulinemia, anti-nuclear antibodies and immune complex glomerulonephritis, which usually becomes evident at around 5 months of age.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…The results presented here appear to contradict a recent study by Zhang et al (36) showing that treatment with anti-HMGB1 antibodies reduced lupus-like disease, including proteinuria and glomerulonephritis, in lupus-prone BXSB mice (36). Lupus in BXSB mice is characterized by lymph node and spleen enlargement, hypergammaglobulinemia, anti-nuclear antibodies and immune complex glomerulonephritis, which usually becomes evident at around 5 months of age.…”
Section: Discussioncontrasting
confidence: 56%
“…Therefore, because of high levels of HMGB1 locally, the dose of mAb 2G7 used here may have been insufficient to neutralize HMGB1 completely. Although we cannot exclude this possibility, previous studies in BXSB lupus mice and a sepsis model have clearly shown a positive effect of anti-HMGB1 antibody treatment, despite the development of splenomegaly (21,36).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Administration of monoclonal anti-HMGB1 antibodies have shown opposing effects in animal models of lupus [83,84]. In animal models of arthritis anti-HMGB1 treatment have attenuated the disease [85,86].…”
Section: Antibodies Against High Mobility Group Box Protein-1 (Hmgb1)mentioning
confidence: 99%
“…Studies in animal models of arthritis have shown that treatment with anti-HMGB1 antibodies can attenuate disease by blocking pro-inflammatory actions of HMGB1 [85,86]. Opposing effects of anti-HMGB1 have been demonstrated in two different murine lupus models [83,84]. HMGB1 has different…”
Section: Antibodies Against High Mobility Group Box Protein-1 (Hmgb1)mentioning
confidence: 99%